Expert leaders in a fast-moving environment - Amanda H. Goodall; Ganna Pogrebna (Institute for the Study of Labor (IZA), 2012)
This paper is an attempt to understand the effects of leaders on organizational performance. We argue for an expert leader model of leadership. We differentiate between four kinds of leaders according to their level of inherent knowledge and industry experience. After controlling for confounding variables, teams led by leaders with extensive knowledge of the core business perform better than others. Our study collects and analyses 60 years of data from one of the world's most competitive high-technology sectors (Formula 1 competition) in which each organization's performance can be measured objectively. We show that the most successful team leaders in F1 motor racing are more likely to have started their careers as drivers and mechanics compared with leaders who were principally managers or engineers with degrees. There is a notable association between driving and later success as a leader. Within the sub-sample of former drivers, those with the longest driving careers go on to be the most successful leaders.
Keywords: J33; M5; D22; O32; J24; 330; expert leaders; leadership; organizational performance; high-tech; teams; Führungskräfte; Sachverständige; Berufserfahrung; Führungsstil; Unternehmenserfolg; Motorsport; Welt